Needs Analysis to Develop the Materials for English as a General Course for Non-English Department Students - Normawati, Afi; Nugrahaeni , Dwitiya Ari (Universitas Nusantara PGRI Kediri, 2023)
Developing appropriate resources for a language learning programme, including those for English as a general course, is pivotal in order for the students’ learning to be successful. Prior to the development, the students’ needs should be assessed so that the materials developer obtains a comprehensive view of what the students need. This study aims to investigate the students’ needs to develop the materials for English as a general course for non-English Department students. The research was conducted at Universitas Tidar and involved 240 students from different departments. Quantitative research was employed as the approach of the study, and the data were collected by using a questionnaire. The findings show that the students are motivated to learn English for their potential careers in the future and for global communication. In addition, the students claim that they need to master listening, speaking, reading, and writing skill, as well as grammar and pronunciation. Further, the students consider listening as the most difficult macro skill to master and grammar as the most challenging language aspect to learn. Meanwhile, in relation to the topics, English for everyday, academic, and professional purpose are among the points that should be covered in the materials. In regard to the activity design, in-class activities that the students are most enthusiastic about are practicing pronunciation, learning vocabulary, and watching English-language videos; meanwhile, the students prefer to create videos and work on a project as their assignment. Moreover, they feel enthusiastic when working in groups rather than working in pairs and individually.